2010
DOI: 10.4269/ajtmh.2010.09-0417
|View full text |Cite
|
Sign up to set email alerts
|

The SYBR Green I Malaria Drug Sensitivity Assay: Performance in Low Parasitemia Samples

Abstract: INTRODUCTIONFast and reliable in vitro growth assessment of malaria parasites is the key to the assessment of in vitro drug susceptibility of malaria parasites, and to high throughput screening of newly developed drugs and drug combinations. Although there are several highly sensitive assays available today, the time and effort necessary to test a single microtiter plate remains substantial. Our goal was to assess the value of the SYBR Green I dye for drug susceptibility testing in Plasmodium falciparum cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 11 publications
1
52
0
3
Order By: Relevance
“…This indicates that the WWARN assay is robust and high quality within this range of parasitemia, which directly correlates to the consistent IC 50 s determined and the high success rate of the assay within the range of 0.075% to 0.6% initial field sample parasitemia. Further, a wider RFU range of Ͼ10-fold difference was attained in a comparison of signal from untreated wells and background from highest-drug (kill)-concentration wells, contrary to previously reported RFU signal ranges (12,16). This allowed for easy fitting of dose-response curves and accurate depiction of IC 50 s across parasitemia levels.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This indicates that the WWARN assay is robust and high quality within this range of parasitemia, which directly correlates to the consistent IC 50 s determined and the high success rate of the assay within the range of 0.075% to 0.6% initial field sample parasitemia. Further, a wider RFU range of Ͼ10-fold difference was attained in a comparison of signal from untreated wells and background from highest-drug (kill)-concentration wells, contrary to previously reported RFU signal ranges (12,16). This allowed for easy fitting of dose-response curves and accurate depiction of IC 50 s across parasitemia levels.…”
Section: Discussionmentioning
confidence: 82%
“…This is troublesome, as Chaorattanakawee et al (15) has reported that about 49% of Cambodian and 22% of Kenyan natural infections had parasitemia levels of Ͻ0.2%, depicting large variations in parasite density across the different transmission regions (15). However, with the limit of detection of 0.20% in white blood cell (WBC)-free culture and 0.55% in whole blood (16), the original SYBR green assay technique is inapplicable to screening of most of the isolates found in these regions by immediate ex vivo technique (i.e., patient to assay plate without the need for in vitro culture before assaying). As the SYBR green I drug sensitivity assay based on the WWARN procedure continues to be widely adopted by field-based laboratories, we examined this assay for its sensitivity and ability to accurately determine IC 50 s in samples with a wide range of initial parasitemia levels.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The SYBR green I (SG) dye-based fluorescence assay is a recently developed high-throughput screening method which has been reported to be as sensitive as the [ 3 H]hypoxanthine incorporation assay (8, 10). It has been extensively validated and compared with other known methods and is commonly used for high-throughput antimalarial drug screening (9,(11)(12)(13).…”
mentioning
confidence: 99%
“…The SYBR green I (SG) dye-based fluorescence assay is a recently developed high-throughput screening method which has been reported to be as sensitive as the [ 3 H]hypoxanthine incorporation assay (8, 10). It has been extensively validated and compared with other known methods and is commonly used for high-throughput antimalarial drug screening (9,(11)(12)(13).Peptides and DNA intercalating agents have been widely tested for their antimalarial activity (14-17). Some cell-penetrating peptides (CPPs), e.g., TP10 (18), and a number of DNA intercalators have been shown to have antimalarial activity (16,17).…”
mentioning
confidence: 99%